PEKAN KERLIN: Peran Kader dalam Penempelan Stiker P4K - Rayani, Gusti Nur; Haryono, Ika Avrilina; Nurliani, Siti (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Problems faced by partners related to the role of cadres in attaching P4K stickers at the Babirik Health Center include the lack of community understanding of the importance of the health information provided. Although cadres have tried to attach stickers in strategic locations, community response is often minimal, so that the information is not effective in raising awareness. In addition, cadres also face challenges of limited time and resources, which prevent them from conducting further socialization. The solutions carried out are educating cadres to conduct pregnant women screening; documenting high-risk pregnant women; educating high-risk pregnant women on knowledge; attaching P4K stickers in the homes of high-risk pregnant women. The conclusion from the results of community service activities related to the role of cadres in attaching P4K stickers at the Babirik Health Center shows that this initiative has succeeded in increasing community awareness of maternal and child health. Through the attachment of stickers in strategic locations and the active involvement of cadres, important information about health services becomes more easily accessible and understood by the community. More intensive interaction between cadres and the community shows an increase in requests for information and participation in health programs.